2017
DOI: 10.1097/mib.0000000000001168
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Thiopurine Therapy in Inflammatory Bowel Disease Among 2 Real-life Intercept Cohorts

Abstract: Article first published online 14 June 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 25 publications
1
22
1
1
Order By: Relevance
“…This difference annulled in a secondary analysis with adjustment for dose and metabolite levels, therefore an interdrug difference between AZA and MP seems unlikely. Also, other studies showed a relatively higher dose and leucopenia rate in patients on MP compared to AZA . The difference might be attributed to the absence of MP tablets with a content of 25 mg, which allow a more personalised dosing.…”
Section: Discussioncontrasting
confidence: 85%
“…This difference annulled in a secondary analysis with adjustment for dose and metabolite levels, therefore an interdrug difference between AZA and MP seems unlikely. Also, other studies showed a relatively higher dose and leucopenia rate in patients on MP compared to AZA . The difference might be attributed to the absence of MP tablets with a content of 25 mg, which allow a more personalised dosing.…”
Section: Discussioncontrasting
confidence: 85%
“…Recent: Most recent laboratory measurement in patients continuing therapy or laboratory measurement right before cessation of therapy in patients with long-standing remission N: number of available test results. CRP: c-reactive protein, reference interval <8 mg/L FCP: fecal calprotectin, reference interval <35 µg/g SCCAI: simple clinical colitis activity index [21] MAYO: MAYO endoscopic score [26] In this cohort, we showed that the majority (69%) of the patients included were able to tolerate either TG or MTX therapy for over one year, which helps subside the concerns of severe adverse events associated with this rescue UC-therapy, as this percentage is similar to that observed in patients using conventional thiopurines. [10,21] Whereas the observed risk of developing NRH in this cohort was slightly higher than the background prevalence (3-6%), we did not find associated symptomatic pathology in four out of the five patients diagnosed with NRH, which is in line with earlier reports concerning the discrepancies of histological diagnosis with clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…31 Currently, therapeutic drug monitoring (TDM) of thiopurine metabolites may be used to increase clinical efficacy and reduce drug associated toxicity. 32,33 In this procedure, 6-thioguanine nucleotides (6-TGN) and 6-methylmercaptopurine (6-MMP) metabolites are measured and related to therapeutic response and adverse events, respectively. [34][35][36] The definite role of routine measurements of 6-TGN and 6-MMP levels in the management of IBD has not been well established yet.…”
Section: Role Of Tdm Of Azathioprine Metabolites In Ibdmentioning
confidence: 99%